2015
DOI: 10.1016/j.jcgg.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Infection-related stress phenomenon induced takotsubo cardiomyopathy mimicking ST elevation myocardial infarction

Abstract: a b s t r a c tTakotsubo cardiomyopathy is a recognized cardiac syndrome that mimics acute coronary syndrome, without occlusion of the coronary artery. This syndrome is usually triggered by emotional or physical stress. Acute infection as a trigger condition is rarely reported. We report a case of an elderly woman who experienced chest pains with ST-segment elevation on electrocardiography, and who was later confirmed to have this cardiac syndrome by cardiac catheterization in coexistence with shock status rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Another contributor of TS to be considered is acute infection. 17 Although her SARS-CoV-19 swabs were negative, data have shown that the sensitivity of nasopharyngeal swabs decreases as the disease progresses. 18 The clinical suspicion remained high as she presented with a 4-day history of cough and pyrexia along with classical CT changes which suggest SARS-CoV-19 infection with no other cause being found.…”
Section: Discussionmentioning
confidence: 99%
“…Another contributor of TS to be considered is acute infection. 17 Although her SARS-CoV-19 swabs were negative, data have shown that the sensitivity of nasopharyngeal swabs decreases as the disease progresses. 18 The clinical suspicion remained high as she presented with a 4-day history of cough and pyrexia along with classical CT changes which suggest SARS-CoV-19 infection with no other cause being found.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, an infection may be the cause. Severe infection can cause above-mentioned physiological response and theoretically may precipitate TTC in susceptible individuals [8] . In this case, we did not find any emotional stressor.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by apical ballooning and transient left ventricular dysfunction, which usually improves within a few days or weeks. Although this condition is most commonly seen in postmenopausal women typically after an emotional stressor, it has also been reported in younger individuals, men, and even children [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism contributing to this condition remains undescribed, catecholamine surge has been shown to have a role in precipitating TTCM [2][3]. Several infections have also been shown to precipitate TTCM; however, there have been very few cases describing its association with liver abscess [4][5][6][7]. We present a rare case of Takotsubo cardiomyopathy precipitated by the liver abscess.…”
Section: Introductionmentioning
confidence: 90%